Analysis Factors Affecting Lenders Intention In P2p Lending Platform Using Utaut2 Model - et.al, Angelina (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Peer-to-Peer (P2P) lending platform is relatively new to Indonesian market and it managed to dominate Financial Technology in Indonesia by 2019. This fast growth is influenced by simple borrowing and lending activity regulation compared to more traditional markets like banks. Most of previous studies had been focusing on borrowers’ side whereas the lender's side was minimally highlighted. Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) is used to analyze key factors that affect the usage of P2P Lending with addition of trust and risk. This research used SmartPLS to calculate the effect of each variable and found that effort expectancy, social influence, facilitating condition, trust, and risk have positive effects on lenders intention to use the P2P lending platform